2009
DOI: 10.2989/ajar.2009.8.4.7.1044
|View full text |Cite
|
Sign up to set email alerts
|

The importance of interdisciplinary collaborative research in responding to HIV/AIDS vulnerability in rural Senegal

Abstract: HIV prevalence in Senegal is less than 1%, a success generally attributed to the country's quick response to the nascent epidemic of the 1980s and its continued efforts to curtail the spread of HIV. However, as the bulk of the healthcare infrastructure and support for HIV-positive individuals and AIDS patients are located in urban areas, there remains limited information on HIV and AIDS prevalence in rural areas. Several focus group discussions held with small-holder farmers in 2006, in the regions of Kolda an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, it could be argued that these results may not be generalisable to Islamic communities where abstinence from sex until marriage is the norm. Besides, previous research has shown that the interventions which incorporate a community's social norm are more likely to be accepted and more extensively implemented (Marston & King, 2006 ; Willems, 2009 ). Despite these arguments, the findings of these meta-analysis studies highlight the importance of adopting a more comprehensive approach to HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…However, it could be argued that these results may not be generalisable to Islamic communities where abstinence from sex until marriage is the norm. Besides, previous research has shown that the interventions which incorporate a community's social norm are more likely to be accepted and more extensively implemented (Marston & King, 2006 ; Willems, 2009 ). Despite these arguments, the findings of these meta-analysis studies highlight the importance of adopting a more comprehensive approach to HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, previous research has shown that the interventions which incorporate a community's social norm are more likely to be accepted and more extensively implemented (Marston & King, 2006;Willems, 2009). The abstinence-plus approach has the advantage of respecting the conservative communities' religious values and social norms while addressing health professionals' scientific and ethical concerns against AOUM programs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that interventions solely focusing on sexual risk reduction and neglecting abstinence run a risk of becoming rejected since they are regarded as potentially promoting premarital sex in Muslim communities (Elshiekh et al 2021;Kamarulzaman, 2013). Therefore, incorporating abstinence, a religious obligation and highly valued norm in Muslim communities (Elshiekh et al, 2021;Horanieh et al, 2020), could promote religious leaders' support and facilitate programs implementation (Willems, 2009).…”
Section: Introductionmentioning
confidence: 99%